Riežupes dabas parka pilnveidošana Kuldīgas novadā - Serdjukova, Santa (Latvijas Universitāte, 2018)
Daba ir vieta, kur cilvēki vēlas patverties no ikdienas steigas un atjaunot spēkus, jo daba sniedz unikālu iespēju – izbaudīt klusumu un mieru. Tā kā Latvijas daba priecē ne tikai Latvijas iedzīvotājus, bet arī tūristus ar savu krāšņumu un unikalitāti, tad informācijas pieejamība par dabas parkiem ir svarīga, lai cilvēkiem būtu iespēja iekļaut to apmeklējumu savos tūrisma maršrutos. Maģistra darba “Riežupes dabas parka pilnveidošana Kuldīgas novadā” mērķis ir nodrošināt Latvijas iedzīvotājiem un tūristiem iespēju iegūt informāciju par Kuldīgas novadā esošo Riežupes dabas parku. Maģistra darba ietvaros tika veikts pētījums, kurš sastāv no divām daļām – ekspertu intervijas un iedzīvotāju aptauja izmantojot anketēšanas metodi. Pētījuma rezultātā tika noteikta problēma: “Neizstrādāti informatīvie materiāli par Riežupes dabas parku”. Problēmas risināšanai tika izstrādāts projekts, kura ietvaros tika izveidota reklāmas kampaņa par Riežupes dabas parku. Maģistra darba apjoms ir 64 lapas, tas satur 36 pielikumus, 21 attēlus, 6 tabulas un 43 izmantotās literatūras avotus. Atslēgvārdi: dabas parks, tūrisms, Kuldīgas novads, projekts, projekta vadīšana. Nature is a place where people can relax from the daily rush and rebuild their forces, because nature offers a unique opportunity – to enjoy calm and peace. As the nature of Latvia delights not only residents of Latvia but also tourists with its glory and uniqueness, the availability of information about nature parks is important so that people have the opportunity to include a visit to the park on their travel routes. The aim of the Master's thesis "Improvement of the Riežupe Nature Park in Kuldiga District" is to provide residents and tourists with the opportunity to get information about Riežupe Nature Park in Kuldiga District. The research work was carried out in the master's thesis, which consists of two parts - expert interviews and population survey using the questionnaire method. Research results identified a problem: "There are no informative materials about the Riežupe Nature Park. In order to solve the problem a project was developed where an advertising campaign about the Riežupe Nature Park was created. Master’s thesis contains 63 pages, 6 tables, 21 images, 36 attachments and 43 used sources of literature.

Nature is a place where people can relax from the daily rush and rebuild their forces, because nature offers a unique opportunity – to enjoy calm and peace. As the nature of Latvia delights not only residents of Latvia but also tourists with its glory and uniqueness, the availability of information about nature parks is important so that people have the opportunity to include a visit to the park on their travel routes. The aim of the Master's thesis "Improvement of the Riežupe Nature Park in Kuldiga District" is to provide residents and tourists with the opportunity to get information about Riežupe Nature Park in Kuldiga District. The research work was carried out in the master's thesis, which consists of two parts - expert interviews and population survey using the questionnaire method. Research results identified a problem: "There are no informative materials about the Riežupe Nature Park. In order to solve the problem a project was developed where an advertising campaign about the Riežupe Nature Park was created. Master’s thesis contains 64 pages, 6 tables, 21 images, 36 attachments and 43 used sources of literature.
Improvement of Riezupe Nature Park in Kuldiga district
Keywords: Vadībzinātne; dabas parks; tūrisms; projekta vadīšana; Kuldīgas novads; projekts